2000
DOI: 10.1016/s0092-8674(00)00086-6
|View full text |Cite
|
Sign up to set email alerts
|

Src Tyrosine Kinase Is a Novel Direct Effector of G Proteins

Abstract: Heterotrimeric G proteins transduce signals from cell surface receptors to modulate the activity of cellular effectors. Src, the product of the first characterized proto-oncogene and the first identified protein tyrosine kinase, plays a critical role in the signal transduction of G protein-coupled receptors. However, the mechanism of biochemical regulation of Src by G proteins is not known. Here we demonstrate that Galphas and Galphai, but neither Galphaq, Galpha12 nor Gbetay, directly stimulate the kinase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
332
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(346 citation statements)
references
References 74 publications
12
332
0
2
Order By: Relevance
“…This stabilized form of Src shows low basal activity, but ECM components such as fibronectin may activate it by inducing conformational changes (Moarefi et al, 1997;Ma et al, 2000). Moreover, it has been described that Src achieves the conformation accessible for the activating phosphorylation by different signaling molecules, such as Cdc2, only after prior phosphorylation at the Csk-specific Tyr527 residue (Stover et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This stabilized form of Src shows low basal activity, but ECM components such as fibronectin may activate it by inducing conformational changes (Moarefi et al, 1997;Ma et al, 2000). Moreover, it has been described that Src achieves the conformation accessible for the activating phosphorylation by different signaling molecules, such as Cdc2, only after prior phosphorylation at the Csk-specific Tyr527 residue (Stover et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…When phosphorylated at Tyr530, the activity of Src is reduced to low basal levels, thereby protecting cells from the potential oncogenic activity of the src protooncogene (Zheng et al, 2000). The activity of Src phosphorylated at the C-terminal Tyr530 can be increased either by dephosphorylation of Tyr530 or by phosphorylation at other tyrosine residues, for example, after the stimulation of integrin receptors with fibronectin (Moarefi et al, 1997;Ma et al, 2000). It has been shown that Src shows significantly greater protein stability when phosphorylated by Csk (Roskoski, 2004).…”
Section: Re-expression Of Src In Cutl1-knockdown Cells Restores Spreamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we now show that Src plays a critical role in the S1P-stimulated MT1-MMPdependent EGFR transactivation and cell migration. It has been reported that G protein a subunits, such as G ai , directly stimulate Src activity (60), which can lead to MMP-dependent release of EGFR ligands (61). For example, Src activation has been shown to regulate the ADAM-dependent shedding of the L1 adhesion molecule (62).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether AFAP can directly activate c-Src, an in vitro reconstitution assay was performed (23). Briefly, 20 ng of purified and C-terminal Src kinase-inactivated c-Src (a gift from Dr. X. Huang, Cornell University) in Src kinase buffer (30 mM HEPES, pH 7.4, 5 mM MgCl 2 , 5 mM MnCl 2 , and 10 M ATP) was incubated with 2 g of Src substrate peptide (24) and 10 Ci of [␥-32 P]ATP with purified recombinant cAFAP or AFAP71A (22) in a total 20-l reaction volume at 30°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%